Influence of human gut microbiome on the healthy and the neurodegenerative aging - Borrego Ruíz, Alejandro; Borrego-García, Juan José (My University, 2024)
The gut microbiome plays a crucial role in host health throughout the lifespan by influencing brain function during aging. The microbial diversity of the human gut microbiome decreases during the aging process and, as a consequence, several mechanisms increase, such as oxidative stress, mitochondrial dysfunction, inflammatory response, and microbial gut dysbiosis. Moreover, evidence indicates that aging and neurodegeneration are closely related; consequently, the gut microbiome may serve as a novel marker of lifespan in the elderly. In this narrative study, we investigated how the changes in the composition of the gut microbiome that occur in aging influence to various neuropathological disorders, such as mild cognitive impairment (MCI), dementia, Alzheimer’s disease (AD), and Parkinson’s disease (PD); and which are the possible mechanisms that govern the relationship between the gut microbiome and cognitive impairment. In addition, several studies suggest that the gut microbiome may be a potential novel target to improve hallmarks of brain aging and to promote healthy cognition; therefore, current and future therapeutic interventions have been also reviewed.
Keywords: Sistema nervioso - Degeneración; Alzheimer, Enfermedad de; Parkinson, Enfermedad de; Aging; Gut microbiome; Healthy elderly; Mild cognitive impairment; Treatments